PENERAPAN KEBIJAKAN DAERAH TENTANGKEGIATAN JUAL-BELI MAKANAN/MINUMAN DI BULAN RAMADHAN DI KOTA AMUNTAI KABUPATEN HULU SUNGAIUTARA - Akhmad Riduan (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2015)
As a socio-cultural product of Banjar society, Ramadhan seasonal market, which coincided with the month of Ramadhan is a socio-cultural phenomena that reflects the religiosity of society, especially in Amuntai, Hulu Sungai Utara. Along with the globalization influencing Muslim countries, it’s reflecting the cultural change in society of Amuntai, known as Bertakwa City which is the cultural basis of social organization Nahdlatul Ulama and Muhammadiyah. Here, Regulation of Hulu Sungai Utara District No. 32 Year 2013 on the Prevention and Prohibition of Staining Activities in the sacred month of Ramadhan was made to ensure peace and order during the month of Ramadhan.In implementation, it’s constrained by low awareness of the traders / buyers as a target group in addition to the lack of enforcement of sanctions explicitly and the absence of a Standard Operating Procedure (SOP) that also affect the level of performance of the Civil Service Police Unit. In addition, limited land for Ramadan Market location in Jalan Basuki Rahmat resulted in the closure of the road and not the concentration of the traders of food / drinks.To improve the effectiveness of the implementation, it should be carried out intensive monitoring and integrated by forces civil service police unit especially with respect to hours of selling food / drinks during the day in Ramadan seasonal market and in other similar locations, the settings related to the traders cake / small snacks in the market daily / weekly complemented by the determination of the location of Ramadan more representative markets in the coming years by the authorities. In the meantime, it takes continuous socialization coupled with enforcement of sanctions explicitly that all of the stages refers to a set of Standard Operating Procedure (SOP).